Business education and the (re)production of gendered cultures of work in the City of London - Hall, Sarah (Oxford University Press, 2013)
This paper examines the role of business education in producing and legitimating gendered cultures of work in the City of London. By combining research on the gendered nature of service work with Bourdieu's identification of multiple forms of capital and the role of education credentials within this, the analysis shows how business education reproduces classed and gendered understandings of appropriate and desirable workplace personas in financial services. The analysis is based on original empirical research undertaken in London's investment banking sector comprising 90 semi-structured interviews and content analysis of business education courses offered to investment bankers. Empirically, the paper focuses attention on the comparatively neglected role of business education undertaken in the workplace in shaping the cultures of work in financial centers such as London. Theoretically, the analysis shows how work on the cultural capital associated with education credentials and their role in shaping workplace identities can be used to better understand the role of education in legitimating, reproducing and sustaining gendered cultures of work more generally.